Exploring the Negative Impacts of Social Media on Modern Society - Abuzar Khpalwak Zazai; Shir Ahmad Hamidi (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This paper investigates the negative effects of social media on mental health, social interactions, and democratic processes, focusing on studies conducted between 2016 and 2023. The purpose of this research is to explore the various ways in which social media platforms contribute to issues like anxiety, depression, addiction, misinformation, and the decline in face-to-face communication. A systematic review methodology was employed, analyzing academic databases and peer-reviewed articles to identify the impact of social media on individuals and society. The results highlight how excessive use of social media exacerbates mental health problems, particularly in adolescents and young adults, fosters addiction, and promotes distorted views of reality, leading to body image issues and self-esteem concerns. Additionally, the study found that social media contributes to political polarization and misinformation, influencing public opinion and behaviors. In conclusion, the paper emphasizes the need for mitigating strategies, such as promoting digital literacy, supporting mental health awareness, and regulating content. These findings underscore the necessity of responsible social media use and further research to address its long-term societal effects.